Comparative investigation of the nutritional value of cow, goat, and sheep white cheeses in brine - Paskas, S; Becskei, Z; Savic, M (Journal of the Hellenic Veterinary Medical Society, 2024)
In the present work, three different types of cheese in brine have been compared based on their nutritional quality parameters. The cheeses were made from cow’s milk (commercial cheese) and goat and sheep milk (traditional cheese). The physicochemical composition, fatty acid profile, amino acid profile, and related health lipid indices of the cheeses were investigated. The study revealed a significant difference (p<0.05) between the cheeses studied in brine in terms of physicochemical composition. In particular, goat and sheep brine cheeses have a higher concentration of dry matter, fat and protein. Conversely, the Ca content was significantly higher (p<0.05) in the commercial cheeses, as was the Ca/protein ratio (mg g-1 protein). The results also highlighted the health-beneficial fatty acid profile of sheep and goat brine cheeses, particularly the more favourable values of the nutritional indices: AI, TI, HPI, HH and n-6/n-3 ratio compared to commercial cow brine cheeses. The lipid composition of goat and sheep brine cheeses contained significantly lower amounts of long-chain saturated fatty acids and higher amounts of short- and medium-chain saturated and polyunsaturated fatty acids. Analysis of the amino acid profile showed that goat brine cheeses were rich in branched-chain amino acids (BCAA) and had the best essential/non-essential amino acid ratio compared to sheep and cow brine cheeses. According to these results, traditional brine cheeses made from goat’s and sheep’s milk have a high nutritional value. To make the production of these cheeses more sustainable, they need to be promoted as valuable sources of health-promoting compounds.